Gotong Royong Reflection in The Content of GOTO Advertising at Youtube - Rustono Farady Marta; Natasia Angreani; Mikhael Wijaya; Nani Kurniasari; Mercedes Amanda (Unisba Press, 2022)
This research aims to understand the meaning of 'Gotong Royong' in GOTO's YouTube video by applying Hofstede's Cultural Dimensions. The world keeps on revolving and more technologies has appeared to make life in all aspects easier. GOTO is a newly merged tech giant of Gojek and Tokopedia as one of the most popular e-commerce in Indonesia. In order to be accepted by society, GOTO creates a creative ad with a philosophical message that not only aims to market their products but also to introduce 'Gotong Royong,' which is the culture of Indonesia. Through Philip Mayring, Qualitative Content Analysis helps us to explain the Hofstede six cultural dimensions through the mixture of visual and audio found in GOTO's. In order the emphasize the “Gotong Royong” culture, by using Philip Mayring Qualitative Content Analysis, the video was divided into parts that represent the audio and visual elements, GoTo's video tries to show a cultural message that is